Here, But Not Now:: A Local Tour of a Global Future in The Afterlife of Buildings - Kaminska, Aleksandra; Nesselroth-Woyzbun, Eva (Material Culture Review)

(untitled) (National Museums of Canada, 2010)
Abstract In this essay we explore the exhibition The Afterlife of Buildings. Artists Nicolas Grospierre and Kobas Laksa craft a portrait of Warsaw’s near future through a manipulation of photographs of six buildings recently constructed in the city, playing upon its post-socialist material expressions of identity. The exhibition was presented in a fictitious "Hotel Polonia"—figuratively inviting viewers to gaze into Warsaw’s future while reflecting upon its history, memory and the precarious and transitioning quality of its present. And yet, in creating a vision of Warsaw’s future the artists have plugged the city into a global narrative on sustainability and the failure of ideological dreams.